Solid State Transformers: A Review—Part I: Stages of Conversion and Topologies - Dragoș-Mihail Predescu; Ștefan-George Roșu (Technologies)
Solid State Transformers (SSTs) represent an emerging technology that seeks to improve upon traditional Low-Frequency Transformers (LFTs) with Medium-Frequency Transformers (MFTs) of reduced core size while incorporating modular converter structures as their input and output stages. In addition to magnetic circuit reduction, SSTs provide enhanced functionalities such as power factor correction, voltage regulation, and the capability to interface with various sources and loads. However, owing to the novelty of SSTs and the various proposed implementations, a general review would difficult to follow and might not be able to adequately analyze each aspect of SST structures. This complexity underscores the need for a new division of information and classification based on the number of conversion stages, which is the main contribution of this study. Converter functionalities are derived based on the number of stages. Utilizing these functionalities along with existing and proposed implementations, converter topologies are identified and then detailed in terms of their respective functionalities, advantages, disadvantages, and control schemes. The subsequent chapters provide a comparative analysis of the different topologies and present existing SST implementations. For this analysis, metrics such as the number of SST stages, power flow, voltage control, power quality, and component count are used. Based on the resulting analysis, single-stage SSTs are a promising solution that emphasize economy and high power density, while multi-stage SSTs are also a viable solution thanks to their ease of control and flexible design. This paper constitutes the first part of a two-part review. The second part will focus on the degrees of design freedom (such as multilevel structures/cells) and provide a generalized approach to modularity within SST systems.